Estimating the Burden of Cost in Chronic Graft-versus-Host Disease: A Human Capital Approach - Chris A. Jones; Luca P. Fernandez; Peter Weimersheimer; Neil A. Zakai; Michael Sharf; Oscar A. Mesa; Christian Peters; Antonio di Carlo; Mitchell C. Norotsky (Journal of Health Economics and Outcomes Research)
With advances in organ matching and preventing acute graft-versus-host-disease (aGvHD), chronic graft-versus-host disease (cGvHD) following allogeneic hematopoietic stem cell transplantation (HSCT) has become a focus of transplant-related morbidity and mortality. Given that cGvHD often presents years following a transplant, our objective was to estimate its burden of cost resulting from allogeneic HSCT based on published estimates of incidence, morbidity, the value of lost work time and survivorship. Our choice of a ten-year time horizon is novel to the field of rare disease and was determined to be meaningful after consultations with present co-authors, including five physicians, one of whom is a transplant surgeon. A total of 44 450 cGvHD patients in the United States were estimated to require treatment over the next decade (from 2015 to 2025). This estimate is based on the last 5 years of trends reported in the transplant registries. What is not reported in any registry is that these patients will accrue a total of 605 631 years of lost wages, a collective lost productivity that will cost society over $27 Billion in the decade ahead: more than five times ($27B vs. $5.2B) the estimated ten-year cost of treating the condition.